The New Global Guidance of Revenue Recognition in the Anglo-Saxon Market (Global Journal of Management and Business Research, 2017)
The purpose of this research study is to provide an understanding of the adoption of revenue recognition in the Anglo-Saxon market. One of the main findings is that the steps involved in revenue recognition mentioned in the literature review should be implemented at the organizational level. Public companies are expected to adopt the new revenue recognition guidelines by 2018. Notably, the FASB will bring a global vision to a new set of accounting rules in the United States. Research limitations indicate organizations are running out of time to adopt the new deadlines proposed by FASB. Any delay in the adoption of revenue recognition will have an impact on companies’ bottom line finances. The participation of tax professionals in the adoption process mentioned above is minimal. Therefore, businesses are expected to be affected directly by the lack of tax professional participation.
Keywords: FASB; IASB; FinRec; USGAAP; IFRS; revenue recognition